2020
DOI: 10.7554/elife.58182
|View full text |Cite
|
Sign up to set email alerts
|

Transcription termination and antitermination of bacterial CRISPR arrays

Abstract: A hallmark of CRISPR-Cas immunity systems is the CRISPR array, a genomic locus consisting of short, repeated sequences ('repeats') interspersed with short, variable sequences ('spacers'). CRISPR arrays are transcribed and processed into individual CRISPR RNAs that each include a single spacer, and direct Cas proteins to complementary sequence in invading nucleic acid. Most bacterial CRISPR array transcripts are unusually long for untranslated RNA, suggesting the existence of mechanisms to prevent premature tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…In serovar Typhimurium str. 14028s, 236 spacer- and Cascade-binding sites were identified using ChIP-seq of Cas5 40 . After mapping these sites on the complete genome of serovar Typhimurium str.…”
Section: Resultsmentioning
confidence: 99%
“…In serovar Typhimurium str. 14028s, 236 spacer- and Cascade-binding sites were identified using ChIP-seq of Cas5 40 . After mapping these sites on the complete genome of serovar Typhimurium str.…”
Section: Resultsmentioning
confidence: 99%
“…boxA could improve RNA polymerase processivity of these and our synthetic arrays (Fig. 4 ) by a number of different mechanisms, one of which may be blocking Rho-dependent transcription termination 52 54 , as hypothesized by Stringer et al 37 . Still, as naturally occurring CRISPR arrays can stretch to the hundreds of spacers 32 , there could be additional unknown factors that regulate spacer transcription that could one day be applied to a CRISPR-based tool.…”
Section: Discussionmentioning
confidence: 60%
“…Recently Stringer et. al reported that boxA elements may be evolutionarily conserved upstream of naturally occurring CRISPR arrays where they appear to promote expression of downstream spacers within long arrays 37 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-crRNAs are amongst the longest non-coding RNAs in prokaryotes next to the 16S and 23S rRNAs. In E. coli , dedicated antitermination complexes ensure processivity of CRISPR array transcription by preventing premature Rho-dependent transcription termination similar to the antitermination complexes facilitating rRNA transcription [4]. Beyond E. coli , little is known about specific mechanisms controlling CRISPR array transcription.…”
Section: Introductionmentioning
confidence: 99%